Analisa Kitab Ihya’ Ulumuddin Perspektif Pemikiran Islam - Badruttamam (Prodi Tasawuf dan Psikoterapi Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2022)
Islamic civilization is strongly influenced by one's worldview. Likewise with the style of work written by an author, scholar or intellectual. The political situation and conditions and government policies really give color to a work. This happened at the time of Muhammad al Ghazali when he lived in the error of the Abbasids. Then a monumental book was born, namely Ihya 'Ulumuddin (turning on the religious sciences). This book was born out of anxiety after experiencing and analyzing the conditions of thought, belief and perception of the people and government at that time. So that in the book al-Ghazali gives signs by dividing into four rubu', namely rubu' worship, rubu' custom, rubu' mukhlikat and rubu' munjiyat. The four rubies ' provide an answer to the unrest that occurs in the Muslims. It is proven that the book of Ihya 'Ulumuddin is still being conveyed and studied to this day among Islamic boarding schools and educated people.